Human resource management - Dessler, Gary. (Chennai India ; Pearson Education, 2016)
"Human Resource Management addresses the study of HR in a realistic, practical, and stimulating manner. Examples of how HR management is practiced in the real world and the relationship between various HR topics are interwoven throughout the text, giving students a thorough introduction to the field based on sound theoretical concepts and practice. The Fourteenth Edition reveals HR's strategic importance to management and the overall health of an organization. The text also addresses the ongoing shrinkage of internal HR departments as many companies shift towards HR outsourcing, HR shared service centers, and professional employer organizations. Students should walk away with an appreciation for how the HR profession continues to shed its administrative image and while focusing on mission-oriented activities"
Part I. Setting the Stage : -- 1. Human Resource Management: An Overview -- 2. Business Ethics and Corporate Social Responsibility -- 3. Equal Employment Opportunity, Affirmative Action, and Workforce Diversity -- Part II. Staffing : -- 4. Strategic Planning, Human Resource Planning, and Job Analysis -- 5. Recruitment -- 6. Selection -- Part III. Performance Management and Training : -- 7. Performance Management and Appraisal -- 8. Training and Development -- Part IV. Compensation : -- 9. Direct Financial Compensation (Core Compensation) -- 10. Indirect Financial Compensation (Employee Benefits) - - Part V. Labor Relations, Employee Relations, Safety, and Health : -- 11. Labor Unions and Collective Bargaining -- 12. Internal Employee Relations -- 13. Employee Safety, Health, and Wellness -- Part VI. Operating in a Global Environment : -- 14. Global Human Resource Management.
Keywords: Personnel management